Realizing Sustainable Development Goals (SDGs) by Reviving Mosque Functions in Family Guidance - M. Ilham Muchtar; Muktashim Billah (Family Law Study Program (Ahwal Syakhshiyah), Universitas Muhammadiyah Makassar, 2022)
Mosques have a great deal of potential for supporting Muslim families. However, there are still a lot of mosques that do not fully utilize this excellent opportunity. In order to shed light on this issue, a literature review titled